The Value Pluralism From Taha Abderahman's Prespective - Djegham , Hadda (Journal of Social Sciences and Humanities, 2025)
Our present Era has witnessed a grouting debate on Value issuer ;as they relate to all aspects of Human life uncluding the wrrent inbalances in reference and balance ,it's absence at some has led to a conflict and collission of values and various emered ,uncluding values pluralism . The Thinker Taha Abderahman looks at the side of worality and values ,truying to bring it back to its Islamic Sources .He looks at the saying :The inltiplicity of vales and their confrontation in western thought . He analyses and criticises it in order to provide it with evidence .He calls "The enconter of values " truying to get of the cycle of conflict .